A summary of the use of maize in nutritional products for sportsmen - Kinga Kostrakiewicz-Gierałt (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2020)
The aim of the investigation was to review experimental articles and patents referring to corn-based nutritional products for sportspeople published in the period 19702019. Publications were searched in the ISI Web of Science and Scopus databases, as well as the Google Scholar and Google Patents internet search engines. Factorial combinations of the keywords ("Zea mays" or "maize" or "corn") and ("athlete" or "sport") were applied. Most papers and patents were published in the period 2010-2019 by researchers affiliated to the USA and China - the two largest global producers of corn. Altogether, 65 patents and 16 articles were recorded. Inventors patented food supplements based on corn-derived saccharides and proteins. Empirical articles were devoted to the impact of corn-based food products on health of sportspeople, evaluation of the impact of length of consumption on the metabolism and performance of athletes, as well the frequency of use and acceptance of nutritional products based on corn by sportspeople. Despite growing interest in the application of corn constituents in nutritional products for sportspeople, further investigations are strongly desirable.